2015
DOI: 10.1039/c5cp01377a
|View full text |Cite
|
Sign up to set email alerts
|

Photo-thermal effects in gold nanoparticles dispersed in thermotropic nematic liquid crystals

Abstract: The last few years have seen a growing interest in the ability of metallic nanoparticles (MNPs) to control temperature at the nanoscale. Under a suitable optical radiation, MNPs feature an enhanced light absorption/scattering, thus turning into an ideal nano-source of heat, remotely controllable by means of light. In this framework, we report our recent efforts on modeling and characterizing the photo-thermal effects observed in gold nanoparticles (GNPs) dispersed in thermotropic Liquid Crystals (LCs). Photo-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 40 publications
1
36
0
Order By: Relevance
“…Among the various inorganic (e.g., metal and carbon nanomaterials) and organic (e.g., indocyanine green and polyaniline) photothermal agents, gold nanoparticles and graphene have attracted particular attention due to their high photothermal conversion efficiency as well as their NIR-absorbing spectra, which make them extraordinarily popular in biological applications [277][278][279][280]. Remote manipulation of LCs through the photothermal effects induced by particular nanomaterials is an emerging field of promising materials [281][282][283][284][285]. The functional nanoparticle-LC composites are driven by light when the photothermal nanomaterial absorbs the light energy and converts it into heat, leading to a local increase in temperature.…”
Section: Photonic Applicationsmentioning
confidence: 99%
“…Among the various inorganic (e.g., metal and carbon nanomaterials) and organic (e.g., indocyanine green and polyaniline) photothermal agents, gold nanoparticles and graphene have attracted particular attention due to their high photothermal conversion efficiency as well as their NIR-absorbing spectra, which make them extraordinarily popular in biological applications [277][278][279][280]. Remote manipulation of LCs through the photothermal effects induced by particular nanomaterials is an emerging field of promising materials [281][282][283][284][285]. The functional nanoparticle-LC composites are driven by light when the photothermal nanomaterial absorbs the light energy and converts it into heat, leading to a local increase in temperature.…”
Section: Photonic Applicationsmentioning
confidence: 99%
“…Pezzi et al studied the photothermal effect of gold nanoparticles in thermotropic nematic LC (NLC) phases both experimentally and theoretically . They characterized the photothermal effect of gold nanoparticles doped into thermotropic LCs and subsequently modeled the observations.…”
Section: Liquid Crystals Driven By Photothermal Effectmentioning
confidence: 99%
“…Their tiny size allows their use in subwavelength applications, such as nanoscale sensors [13]. Several studies have reported recently where LSRP has been used as the basic mechanism for obtaining sensors combined with liquid crystals [27,28], holographic structures of polymers with LC, and the named POLICRYPS [29]. A new field has arisen named plasmomechanics that exploits the strain properties of PDMS doped with AuNP [30].…”
Section: Introductionmentioning
confidence: 99%